Treatment options for impacted maxillary canines and occurrence of ankylotic and resorptive processes: a 20-year retrospective study - Pavlina Cernochova; Cenek Cernoch; Karin Klimo Kanovska; Emil Tkadlec; Lydie Izakovicova Holla (BMC, 2024)
Abstract Background This 20-year retrospective study aimed to evaluate the treatment methods used in patients with impacted maxillary permanent canines and to determine the occurrence of ankylotic and resorptive processes and their association with potential risk factors. Methods The cohort consisted of 351 consecutive Caucasian patients (120 males and 231 females, mean age 18.4 and 19.9 years, respectively) with 420 impacted maxillary permanent canines. CT and CBCT findings were subsequently confirmed during surgery. Statistical analyses were performed by the generalized linear models, Pearson x2 and Fisher exact tests using the statistical programs R and Statistica v. 14. Results A total of 273 (65.0%) impacted canines were aligned in the dental arch by orthodontic traction after surgical exposure, this treatment was predominant in patients under 20 years of age. Surgical extraction was performed in 115 (27.2%) impacted canines and was more common in older patients. Ankylotic changes were recorded in 61 (14.5%) impacted canines. The probability of ankylosis increased with age, particularly after the patient's 20th year of life (p < 0.001). Patients were 1.2% likely to develop ankylosis at age 15 years, 4.3% at age 20 years, 14.1% at age 25 years, and 96.8% at age 45 years. Invasive cervical root resorption (ICRR) was found in 8 (1.9%) canines. In 4 canines (1.0%), root ankylosis in addition to ICRR was observed. In contrast to ankylosis, whose frequency of occurrence increased with age, the occurrence of ICRR resulting from PDL damage during surgery was more typical in younger patients. Canines in a high position above the root apices of the adjacent teeth, with a horizontal inclination of the longitudinal axis, with the crown located deep in the center of the alveolar bone and with labiopalatal position, should be considered critically impacted canines with a high risk to failure of orthodontic traction. Conclusion In conclusion, the treatment of impacted canines depends mainly on the age of the patient, and the position and inclination of the longitudinal axis of the impacted tooth. To select an adequate treatment method, we recommend CBCT examination, which allows a precise analysis of the position of impacted canines.